Manejo de la pudrición radical (Phytophthora cinnamomi rands) del aguacate (Persea americana linneo) (2014)
To find new strategies for the management of avocado root rot, it was evaluated potassium phosphite, Metalaxyl + Mancozeb, Fosetyl-Al + Mancozeb, Trichoderma harzianum and mulch prepared with sugar cane bagasse rich in cellulose. The study was conducted at CORPOICA, Palmira. It was characterized the isolates Ag-037 and Ag-040, as Phytophthora cinnamomi. The experiment consisted of six treatments, in a randomized complete block design with three replications, using a split plot arrangement with two types of fertilization (chemical and integrated), The experimental unit consisted of nine seedlings of the Waldin variety. Seedlings of month old were inoculated with P. cinnamomi at a concentration of 1x105 sporangia per mL and the substrate was performed in three holes at 5 cm from the root collar y applied 20 mL of the suspension for seedling. The treatments were applied one month after of inoculation and three applications were made every 30 days. Disease incidence, population of P. cinnamomi in the soil, disease severity, seedling height, dry weight and enzyme activity of cellulose were evaluated at 6, 12 and 18 weeks after the inoculation. The root rot incidence in avocado seedlings was 100%, but the disease severity, ranged between 5% and 22%. Overall, the reduction in disease severity was of 35%. The treatments with Metalaxyl + Mancozeb, Fosetyl-Al + Mancozeb and Potassium phosphite reduced in 42% the population of P. cinnamomi in the soil and in 50% the disease severity, these treatments increased 28% the height and 66% the dry weight of the seedlings